2008
DOI: 10.1111/j.1365-2753.2007.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing walking speed in clinical research: a systematic review

Abstract: Tests of walking speed have been used in a wide range of populations. However, methodologies and descriptions of walking tests vary widely from study to study, which makes comparison difficult. There is a need to find consensus for a standardized walking test methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
268
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(275 citation statements)
references
References 110 publications
1
268
0
6
Order By: Relevance
“…Walking speed is often measured in clinical practice as part of a comprehensive geriatric assessment (CGA) (Peel et al 2013) and in clinical research (Graham et al 2008a). It is a quick and easy measure and is not limited to specific equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Walking speed is often measured in clinical practice as part of a comprehensive geriatric assessment (CGA) (Peel et al 2013) and in clinical research (Graham et al 2008a). It is a quick and easy measure and is not limited to specific equipment.…”
Section: Introductionmentioning
confidence: 99%
“…They were asked to walk normally, even when using walking aids. 16 A speed of less than 0.8 m/s was considered a risk for sarcopenia. 2,15 The second test required the participant to lift themselves from a chair without using their arms and walk three meters at a comfortable, safe pace, before turning around, walking back and sitting down again.…”
Section: Assessment Of Functional Performancementioning
confidence: 99%
“…If it is recommended to acquire the data at the same time (that is, during the same observed/timed10-m walk), the use of a dynamic start is not possible for standardized WISCI II testing. While some authors 41 recommend a dynamic start with 2 m of acceleration before measurement of walking speed, others 42 state that the static start with no acceleration is adequate. In a systematic review of walking speed research in neurological diseases, 42 it was concluded that the static start is the preferred method for the 10MWT.…”
Section: Resultsmentioning
confidence: 99%
“…While some authors 41 recommend a dynamic start with 2 m of acceleration before measurement of walking speed, others 42 state that the static start with no acceleration is adequate. In a systematic review of walking speed research in neurological diseases, 42 it was concluded that the static start is the preferred method for the 10MWT. In addition, Scivoletto 43 has shown that in chronic incomplete SCI patients, walking speed with a static start does not differ significantly (P ¼ 0.092) from walking with a dynamic start.…”
mentioning
confidence: 99%